The Correlation Between Emotional Intelligence and Speaking Skill of EFL Students - Miftha Imama, Annifa; Wilany, Eka (Foreign Language Instruction Probe, 2023)
This study aimed to find the correlation between Students’ Emotional Intelligence and students’ speaking skill at the eighth grades of SMP Islam Nurul Haq Batam. In this study, the population was 50 students, and the samples were 30 students. The researcher employed simple random sampling for technique sampling. In collecting the data, the researcher used questionnaires to assess students’ emotional intelligence adapted from HRB (Health Research Board) by NHS London Leadership Academy (2014), which consisted of 29 items of questions, and the speaking test was to measure students’ speaking skill. The researcher used the Shapiro-Wilk formula to test the normality of the data and Hartley's test to verify the homogeneity of the data before assessing the hypothesis. To determine the relationship between the two variables researched, the researcher used the Pearson Product-Moment Correlation formula. The result of this research showed that rcount was higher than rtable (0.468> 0.361), with a significance level of 0.05; n = 30. It signified that the null hypothesis (H0) was rejected, whilst the alternative hypothesis (Ha) was accepted. In decision, there was a considerable relationship between emotional intelligence and students’ speaking skill. Teachers should emphasize emotional intelligence in students' learning to enhance speaking skills.